2015
DOI: 10.5935/1984-6835.20150071
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sodium Bentonites: Effect of Treatment with Ammonium Salt-Free Organic Surfactant

Abstract: Bentonites, which the main clay mineral is montmorillonite, are commercially attractive because of its abundance in nature. The clays can be modified by ion exchange reactions of ions contained in the interlayer region with cationic surfactants that include ammonium or phosphonium salts. The clays origin and the type of surfactants (modifiers) are the main factors in the alteration of physical and chemical properties of these materials. This study aims to characterize and compare the results of natural bentoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Both organoclays and sodium bentonite Vulgel CN 45 had their physical and chemical properties characterized and disclosed in previous work [27] . In that work, the authors reported that the BN-AM showed the lower iron content and it was considered, among the other studied organoclays, the more promising one for nanocomposite use in nanocomposite preparation.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…Both organoclays and sodium bentonite Vulgel CN 45 had their physical and chemical properties characterized and disclosed in previous work [27] . In that work, the authors reported that the BN-AM showed the lower iron content and it was considered, among the other studied organoclays, the more promising one for nanocomposite use in nanocomposite preparation.…”
Section: Methodsmentioning
confidence: 84%
“…The novelty of the present work is the addition of a new organoclay synthetized with a non-ionic surfactant, free of ammonium salt, which makes it more environmentally friendly [27][28][29] . BN-AM was added to an EVA matrix and the system characterized by WAXD, rheological and thermal analyzes and the results obtained were compared to similar systems containing a traditional organoclay.…”
Section: Introductionmentioning
confidence: 99%
“…The montmorillonite clays were donated by Mineral Technology Centre (CETEM), Federal University of Rio de Janeiro, Cidade Universitária, Rio de Janeiro/RJ, Brazil. The clays were collected in Boa Vista, Paraíba, Brazil, from different sites named “bofe” and “chocolate.” Both were physically and chemically treated at CETEM/UFRJ in order to promote cation exchange of the exfoliated clay lamellae with cationic surfactants, so the clays present a hydrophobic character …”
Section: Methodsmentioning
confidence: 99%
“…7,e789974669, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.4669 The XRD shows peaks at 20°, 34°, 54°, 62°, 73° and 75°, characteristic of Montmorillonite in the sodium and calcium forms, with a predominance of calcium in the presence of peaks 34°, 62°, 73° and 75°. The peaks between 20° and 30° are quartz and kaolinite residues [Morita et al, 2015;Paiva et al, 2008].…”
Section: Partmentioning
confidence: 99%